2010
DOI: 10.1177/0149206310383909
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating the Burden of Emotional Labor

Abstract: Difficult customer interactions cause service employees to experience negative emotions and to engage in emotional labor. The present laboratory study examined whether social sharing (i.e., talking about an emotionally arousing work event with one’s coworkers) can attenuate the residual anger lingering after a taxing service episode. Participants assumed the role of customer service representatives for a fictitious technical support hotline and encountered either neutral or difficult service interactions. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 85 publications
6
65
1
1
Order By: Relevance
“…Moreover, results indicate that especially social reflexivity represents an important social resource as it buffers the emotional exhaustion and cynicism of emotional dissonance while task reflexivity does not. Our results are in line with those of McCance, Nye, Wang, Jones, & Chiu (), which found that social sharing (i.e. talking about an emotionally stimulating work event with one's coworkers) attenuates the residual anger lingering after a taxing service episode.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, results indicate that especially social reflexivity represents an important social resource as it buffers the emotional exhaustion and cynicism of emotional dissonance while task reflexivity does not. Our results are in line with those of McCance, Nye, Wang, Jones, & Chiu (), which found that social sharing (i.e. talking about an emotionally stimulating work event with one's coworkers) attenuates the residual anger lingering after a taxing service episode.…”
Section: Discussionsupporting
confidence: 92%
“…This deep acting results in more positive outcomes for the organization as well. With respect to positive and negative display rules, employees typically engage in deep acting when responding to positive display rules, and in surface acting when responding to negative display rules (Grandey, 2003;Diefendorff, Richard, & Croyle, 2006;McCance, Nye, Wang, Jones, & Chiu, 2013;Rutner, et al, 2011). Consistent with this information from prior studies, we hypothesize the following:…”
Section: Emotional Laborsupporting
confidence: 74%
“…An experimental study that separates positive feedback and regulation success would be needed to resolve their relative contributions to overcoming the depletion effect. Other sources of recovery, such as social sharing with colleagues, may contribute to the attenuation of negative effects in the absence of positive feedback from the target (Luminet, Bouts, Delie, Manstead, & Rimé, ; McCance, Nye, Wang, Jones, & Chiu, ). Also, previous research has shown that social exchange processes can have both positive (Cohen, Gottlieb, & Underwood, ) and detrimental (Williams, ) effects on resources depending on the valence of relationships.…”
Section: Discussionmentioning
confidence: 99%